EDM machinability and surface roughness analysis of INCONEL 600 using graphite electrodes. Issue 9 (June 2016) - Torres, A.; Puertas, I.; Luis, C.
Abstract Nowadays, graphite is one of the most popular electrode materials in electrical discharge machining (EDM) processes due to the high rate of removal material which reduces machining times. This reduction has a direct impact on the cost of manufacturing the parts. In this research, the influence of EDM parameters and graphite electrode in an INCONEL 600 alloy has been studied for both positive and negative polarity. To do so, the machining performances of the process are evaluated in terms of material removal rate (MRR), electrode wear (EW), and surface roughness (SR). Results confirm that the use of negative polarity leads to higher material removal rate whereas positive polarity is recommended when low values of EW and a good surface roughness are needed. Moreover, values of 22.2854 and 15.3602 mm3 /min are achieved for negative and positive polarity, respectively. Furthermore, an attempt has been made to study the results obtained in economic terms for industrial purposes. To that end, both production costs and production time of the graphite electrode are compared with those obtained for copper electrodes. It will be shown that graphite electrodes and negative polarity are the most economical within the options considered.